Morphological Knowledge and Literacy Acquisition - Nagy, William E.; Carlisle, Joanne F.; Goodwin, Amanda P. (Journal of learning disabilities, 2014)
The purpose of this special issue of the Journal of Learning Disabilities is to bring to the attention of researchers and educators studies on morphology and literacy that either involve students with learning difficulties or have educational implications for teaching such students. In our introduction, we first provide background information about morphological knowledge and consider the role of morphology in literacy, focusing on findings that are relevant for instruction of students who struggle with reading and writing. Next we present an overview of the studies included in this issue, organized by current issues concerning the role of morphological knowledge in literacy. Collectively, the articles in this issue suggest that students with weaker literacy skills tend to lag behind their peers in morphological knowledge but that all students are likely to benefit from morphological instruction. Morphological interventions hold promise, especially for students who face challenges in language learning and literacy, but additional research is needed to provide a basis for informed decisions about the design of effective morphological interventions.